PENGARUH PERSEPSI KEMUDAHAN, FITUR LAYANAN, DAN KEAMANAN TERHADAP NIAT MENGGUNAKAN E-MONEY - Prastiwi Umaningsih, Wahyu; Kusuma Wardani, Dewi (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2020)
This study aims to examine the effect perceived of use, service features and security on intention to use e-money. The method used is multiple regression analysis. The sampling technique used in this study was convinence sampling and 114 data samples. Regression test results show that perceived of used and service features do not affect the intention to use e-money, while security positively affected the intention to use e-money.